Investigation of structural modification of copper nanopowders - Buranbaev, M.Zh.; Aliev, B.A.; Koztaeva, U.P.; Partizan, G.; Nakysbekov, Zh.; Entibekov, Zh. (Recent Contributions to Physics, 2012)
The structure of nano-sized copper powders, before and after irradiation with high-energy electrons in the dose range 1-10 Mrad, has been studied using the methods of electron microscopy, small-angle X-ray scattering and X-ray photography. New structural phases with different lattice types and parameters have been detected.